2019
DOI: 10.1002/jmri.26920
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Diffusion Analysis of Intravoxel Incoherent Motion MRI in Cerebral Small Vessel Disease

Abstract: Background Cerebral intravoxel incoherent motion (IVIM) imaging assumes two components. However, more compartments are likely present in pathologic tissue. We hypothesized that spectral analysis using a nonnegative least‐squares (NNLS) approach can detect an additional, intermediate diffusion component, distinct from the parenchymal and microvascular components, in lesion‐prone regions. Purpose To investigate the presence of this intermediate diffusion component and its relation with cerebral small vessel dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 40 publications
4
66
0
Order By: Relevance
“…Another study utilized the intravoxel incoherent motion (IVIM) method to investigate the intermediate diffusion component using a nonnegative least-squares method to evaluate glymphatic system function. Using this method, values for both parenchymal diffusivity and microvascular perfusion were detected and perivascular fluid motion was evaluated in relation to the glymphatic system ( 43 ). Diffusion study can also be applied not only to the brain parenchyma but also to the CSF space.…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
See 1 more Smart Citation
“…Another study utilized the intravoxel incoherent motion (IVIM) method to investigate the intermediate diffusion component using a nonnegative least-squares method to evaluate glymphatic system function. Using this method, values for both parenchymal diffusivity and microvascular perfusion were detected and perivascular fluid motion was evaluated in relation to the glymphatic system ( 43 ). Diffusion study can also be applied not only to the brain parenchyma but also to the CSF space.…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
“…One study showed the relationship between the volume fraction of the intermediate diffusion component with white matter hyperintensities and enlarged perivascular spaces. This correlation could indicate aberrant amounts of ISF in degenerated tissue or perivascular edema preceding tissue degeneration in cases with small vessel disease ( 43 ).…”
Section: Neurological Diseases Suspected To Be Associated With Glymphmentioning
confidence: 99%
“…movement of interstitial fluid, 140 , 142 BBB leakage, 137 , 143 and vessel tortuosity. 144 Since rarefaction is often linked with one or more of these vascular alterations, the IVIM perfusion measures ( f , D* and fD* ) are rather indicative of microvascular integrity than mere CBF.…”
Section: Mri Methods To Measure Microvascular Rarefactionmentioning
confidence: 99%
“…Intravoxel incoherent motion MRI, which acquires diffusion-weighted images for multiple b values and fits multiple exponentials that typically correspond to capillary perfusion and Brownian motion, has also been extended to assess for glymphatic function (23). The presence of a diffusion component intermediate to parenchymal diffusivity and microvascular perfusion in regions surrounding enlarged perivascular spaces (EPVS) and white matter hyperintensities has been detected, which may relate to regional glymphatic dysfunction (Fig 2A) (24). PVS flows have also been assessed using diffusion tensor imaging techniques.…”
Section: Other Imaging Methods Of Glymphatic Functionmentioning
confidence: 99%